THE EVOLUTION OF LANGUAGE: HOW HUMANS ACQUIRED THE ABILITY TO COMMUNICATE - Usarova Nilufar Yakubovna; Qodirov Ziyodsher Eminjon o'g'li (International Journal on Integrated Education, 2023)
This article explores the fascinating topic of how humans acquired the ability to communicate through language. The author provides a comprehensive overview of the evolution of language, from its origins in primate vocalizations to the development of complex grammar and syntax in modern human societies. The article examines the role of culture, brain development, and social interaction in the evolution of language, and discusses the latest research on the subject. The author also considers the implications of language evolution for our understanding of human nature and the origins of human culture. Overall, this article is an engaging and informative read for anyone interested in the history and development of human communication.